The mental wellbeing of prison staff in England during the COVID-19 pandemic: A cross-sectional study - Johnson, Luke; Czachorowski, Maciej; Gutridge, Kerry; McGrath, Nuala; Parkes, Julie; Plugge, Emma (Frontiers in Public Health, 2023)
Background: COVID-19 is likely to have had an impact on the mental wellbeing of prison staff because of the high risk for infectious disease outbreaks in prisons and the pre-existing high burden of mental health issues among staff. Methods: A cross-sectional study of staff within 26 prisons in England was carried out between 20th July 2020 and 2nd October 2020. Mental wellbeing was measured using the Short-version of Warwick-Edinburgh Wellbeing Scale (SWEMWBS). Staff wellbeing was compared to that of the English population using indirectly standardized data from the Health Survey for England 2010-13 and a one-sample t-test. Multivariate linear regression modelling explored associations with mental wellbeing score. Results: 2534 individuals were included (response rate 22·2%). The mean age was 44 years, 53% were female, and 93% were white. The sample mean SWEMWBS score was 23·84 and the standardised population mean score was 23·57. The difference in means was statistically significant (95% CI 0·09 to 0·46), but not of a clinically meaningful level. The multivariate linear regression model was adjusted for age category, sex, ethnicity, smoking status, occupation, and prison service region. Higher wellbeing was significantly associated with older age, male sex, Black/Black British ethnicity, never having smoked, working within the health staff team, and working in certain prison regions. Interpretation: Unexpectedly, prison staff wellbeing as measured by SWEMWBS was similar to that of the general population. Reasons for this are unclear but could include the reduction in violence within prisons since the start of the pandemic. Qualitative research across a diverse sample of prison settings would enrich understanding of staff wellbeing within the pandemic.